School Conflict in Rural Education in Northeast of Colombia (Docentes 2.0 Journal, 2020)
The school conflict, a problem that affects every educational community, has repercussions that raise concern because its manifestations affect those involved physically, emotionally, and academically. However, the conflict can be taken as an opportunity for personal progress to improve coexistence and optimize institutional processes; Therefore, the objective of the work was focused on characterizing the types of conflict present in different school spaces and their forms of resolution in the Edmundo Velásquez Educational Institution, located in a rural area of ??the Norte de Santander department, Colombia. The research was of a qualitative, descriptive and interpretive approach with a cross-section, the study population is made up of 36 students of the sixth grade of secondary school and the instrument for obtaining information is the participant observation, which allowed recording in a diary of field events, behaviors that alter the school climate. The results show the prevalence of disruptive behaviors in male students, intolerance and the absence of values, while the conclusions show the need to improve interpersonal relationships, promote harmony, generate structural changes of a socio-cultural nature, regulate conflict resolution through educational policies and mitigate situations with negative impact on the entire student body.
Keywords: School coexistence; aggression; violence; disruptive behaviors